The two kinases, AbrC1 and AbrC2, of the atypical two-component system AbrC are needed to regulate antibiotic production and differentiation in Streptomyces coelicolor - Rodríguez, Héctor; Rico, Sergio; Yepes, Ana; Franco-Echevarría, Elsa; Antoraz, Sergio; Santamaría, Ramón I.; Díaz, Margarita (Frontiers in Microbiology, 2015)
Two-component systems (TCSs) are the most important sensing mechanisms in bacteria. In Streptomyces, Two-component systems (TCSs) are the most important sensing mechanisms in bacteria. In Streptomyces, TCSs-mediated responses to environmental stimuli are involved in the regulation of antibiotic production. This study examines the individual role of two histidine kinases (HKs), AbrC1 and AbrC2, which form part of an atypical TCS in Streptomyces coelicolor. qRT-PCR analysis of the expression of both kinases demonstrated that both are expressed at similar levels in NB and NMMP media. Single deletion of abrC1 elicited a significant increase in antibiotic production, while deletion of abrC2 did not have any clear effect. The origin of this phenotype, probably related to the differential phosphorylation ability of the two kinases, was also explored indirectly, analyzing the toxic phenotypes associated with high levels of phosphorylated RR. The higher the AbrC3 regulator phosphorylation rate, the greater the cell toxicity. For the first time, the present work shows in Streptomyces the combined involvement of two different HKs in the response of a regulator to environmental signals. Regarding the possible applications of this research, the fact that an abrC1 deletion mutant overproduces three of the S. coelicolor antibiotics makes this strain an excellent candidate as a host for the heterologous production of secondary metabolites.